Exclusive Breastfeeding as the Foundation for Complementary Feeding: A 2022 Analysis of Nutrition Status Survey (NSS) Lampung Province, Lampung - Nuryati, Elmi; Sisma Novebri (Universitas Negeri Semarang (UNNES) in cooperation with the Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2025)
In Indonesia, supplemental foods are provided to almost 40% of newborns before they are six months old. This study aimed to identify the factors influencing complementary feeding practices in Lampung Province. A cross-sectional design was used, drawing on secondary data from the 2022 Nutrition Status Survey (NSS) of Lampung Province. Data were collected from all districts and cities in the province, consisting of 13 districts and 2 cities, and included children aged 6–23 months. The final sample comprised 2,310 respondents. Data collection involved interviews, anthropometric assessments and physical checks using household and individual questions carried out by qualified local enumerators. The physical examinations assessed nutritional status, including breastfeeding and complementary feeding practices. Anthropometric measurements included body weight, length/height, and mid-upper arm circumference. Multivariate logistic regression was used for data analysis. The results showed that the variable most strongly associated with complementary feeding practices was breastfeeding history (p = 0.001; OR = 2.244; 95% CI: 1.377–3.658). These findings highlight the importance of optimising exclusive breastfeeding up to six months of age, as it supports infants in developing preferences for a wider variety of foods.